Management Information System in Evaluation of BCA Mobile Banking Using DeLone and McLean Model - Astri Ayu Purwati; Zainol Mustafa; Mazzlida Mat Deli (Journal of Applied Engineering and Technological Science (JAETS), 2021)
The investment in information system brings significant impacts on the banking industry because it plays a pivotal role in providing better services and competitive edges. This study evaluated satisfaction level and benefit of the usage of the banking system which is m-Banking using the IS Success Model approach developed by DeLone and McLane in 2003. The population in this study was customers of one of the largest banks in Indonesia, namely Bank Central Asia (BCA) with a sample size of 200 customers. The data were analyzed using Structural Equation Model (SEM) with AMOS. The results showed that the IS Success Model consisting of system quality, information quality and service quality has a significant impact on customer satisfaction in using BCA m-Banking. This study also validates the research conducted by DeLone and McLean (2003) in developing the IS Success Model as a measure of the quality and key to the success of an information system.